Suicide stigma and suicide literacy among Bangladeshi young adults: a cross-sectional study - Jahan, Ishrat; Sharif, Azaz Bin; Hasan, A. B. M. Nahid (Frontiers in Psychiatry, 2023)
Introduction Suicide is a deadly cause due to which many people die in many regions throughout the globe. Due to poor suicide literacy, people are not aware of the consequences of the suicide stigma, which may affect individuals. This study aimed to examine the status of suicide stigma and literacy among young adults in Bangladesh. Methods This cross-sectional study included 616 males and females residing in Bangladesh aged between 18 to 35 years who were invited to complete an online survey. Suicide literacy and suicide stigma among the respondents were assessed by using the validated Literacy of Suicide Scale, and Stigma of Suicide Scale, respectively. Other independent variables that have been found to affect suicide stigma or literacy were included in the current study based on prior research. Correlation analysis was used to assess the relationships between the study's main quantitative variables. Multiple linear regression models were used to assess factors affecting suicide stigma and suicide literacy, respectively, after controlling for covariates. Results The mean literacy score was 3.86. The participants’ mean scores in the stigma, isolation, and glorification subscale were 25.15, 14.48, and 9.04, respectively. Suicide literacy was negatively associated with stigmatizing attitudes (p=0.005). Males, unmarried/divorced/widowed, less educated (below HSC), smokers, less exposure to suicide, and respondents with chronic mental illness had lower suicide literacy and more stigmatizing attitudes. Conclusion The findings suggest that addressing suicide literacy and stigma by developing and executing awareness programs on suicide and mental health among young adults may increase knowledge, decrease stigma, and hence prevent suicide among this population.